Organometallic Rhenium Complexes Divert Doxorubicin to the Mitochondria. Issue 8 (22nd January 2016) - Imstepf, Sebastian; Pierroz, Vanessa; Rubbiani, Riccardo; Felber, Michael; Fox, Thomas; Gasser, Gilles; Alberto, Roger
Abstract: Doxorubicin, a well‐established chemotherapeutic agent, is known to accumulate in the cell nucleus. By using ICP‐MS, we show that the conjugation of two small organometallic rhenium complexes to this structural motif results in a significant redirection of the conjugates from the nucleus to the mitochondria. Despite this relocation, the two bioconjugates display excellent toxicity toward HeLa cells. In addition, we carried out a preliminarily investigation of aspects of cytotoxicity and present evidence that the conjugates disrupt the mitochondrial membrane potential, are strong inhibitors of human Topoisomerase II, and induce apoptosis. Such derivatives may enhance the therapeutic index of the aggressive parent drug and overcome drug resistance by influencing nuclear and mitochondrial homeostasis. Abstract : The road less travelled : Doxorubicin is a strong chemotherapeutic agent known for its exclusively nuclear accumulation. Two organometallic derivatives of Doxorubicin were found to display a novel and unexpected subcellular distribution, with significant uptake into mitochondria. First in vitro studies corroborate an influence on mitochondrial homeostasis. Such derivatives could be relevant in the ongoing quest for chemotherapeutic agents that can be better tolerated.